Understanding the personal and professional needs of the elderly clients in preparing for meaningful retirement years - Rais, Haniza (2012)

(untitled)
Elderly clients are mature and experienced individuals. The fact that they have gone through life for a long period of time, naturally affect their worldview on how life should be for them. As years go by, they will have to accept the reality of their limitations. Issues related to limitations can be enormous as they cover different angles of life such as physical strengths, emotional changes, health deterioration, spiritual beings, etc. Due to inability to function as effective as they used to, elderly clients may find themselves hurt, frustrated, helpless or useless to their family, community or co-workers. Their self expectations and expectations in others can sometimes affect their relationship with people around them such as their spouses, children, families and friends. This study explored the typical issues among the elderly in relation to their personal and professional journey – Issues that potentially impede their enjoyment of life after retirement. Through focus group discussions and in depth interviews, specific needs discovered and supports recognized to provide counselor with tools in charting a more meaningful life at their age. The findings also provide us with appropriate contents for counselors to consider in providing individual and group counseling to elderly clients. Counseling framework for retirement programmes with the elderly will also be proposed.